A heuristic approach to evaluate peri interactions versus intermolecular interactions in an overcrowded naphthalene - Sounak Sarkar (IUCrJ, 2017)
Octachloronaphthalene (OCN), a serious environmental pollutant, has been investigated by charge density analysis to unravel several unexplored factors responsible for steric overcrowding. The topological features of the enigmatic peri interactions contributing to steric overcrowding are qualified and quantified from experimental and theoretical charge-density studies. A new facet in the fundamental understanding of peri interactions is revealed by NCI (non-covalent interaction) analysis. The potential role of these interactions in deforming the molecular geometry and subsequent effect on aromaticity are substantiated from NICS (Nuclear Independent Chemical Shift) and QTAIM (Quantum Theory of Atoms in Molecules) calculations. The eye-catching dissimilarity in the out-of-plane twisting of OCN renders the molecule in an asymmetric geometry in the crystalline phase compared with symmetric geometry in the optimized solvated phase. This is uniquely characterized by their molecular electrostatic potential (MESP), respectively, and is explained in terms of conflict between two opposing forces – peri interactions, and symbiotic intermolecular Cl...Cl and Cl...π contacts.